(untitled) (Journal of Tropical Pharmacy and Chemistry, 2013)
This study aimed to test the activity of active ingredient mouth gel preparation of kalimantan black piper betle leaf extract with the main base of Hydroxy Ethyl Cellulose namely (HEC) as a mucoadhesive polymer that is able to increase the attractive forces between the active material with a layer of mucus that will extend the contact time with the active ingredient tissue targets, moreover would be increase the effectiveness of antimicrobial activity causes inflammation of the gums (gingivitis) and tooth decay (caries). Activities that have been implemented are mouth gel activity assays with Kalimantan black piper betle leaf extract as in- vitro using the agar diffusion method pitting. In testing with active oral gel preparation of black piper betle leaf extract with the main base of Hydroxy Ethyl Cellulose namely (HEC) as in vitro, it can be seen that the sample may provide the inhibitory effect of the fungus Candida albicans and the bacterium Streptococcus mutans in the presence of a clear zone indicated on the medium. Furthermore, at this stage of the dilution of the gel in twice causing decline in the effectiveness of the inhibition of both the fungus Candida albicans and the bacterium Streptococcus mutans. The results of in- vitro testing without dilution is 19.8 mm in bacteria Streptococcus mutans and 34.4 mm in the fungus Candida albicans.